MEMANFAATKAN TEKNOLOGI UNTUK MENGEMBANGKAN DAN MEMPERLUAS PEMASARAN PARA PELAKU UMKM DI DESA PASIRBARU KECAMATAN CISOLOK KABUPATEN SUKABUMI - Gerry Rizky Andrean Supit (STISIP Widyapuri Mandiri Sukabumi, 2023)
Technology is all the meaning that the goods needed for the continuity and comfort of human life. In this very advanced era of globalization, the use of technology has become commonplace for society, one of which is using technology in the buying and selling process. One of them is UMKM actors in Pasirbaru Village, Cisolok sub-district, Sukabumi district. With modern empowerment that focuses on UMKM’s, it is hoped that UMKM actors in Pasirbaru Village can utilize technology as a means to develop their businesses. There are several actors in Pasirbaru Village who still promote their business traditionally. The selling market is not extensive and there is no distinctive feature of their products. Therefore, knowledge and training are needed so that players will be ready for facing global market and improve the quality of their products and increase their production capacity. The aim is to find out to what extent the Pasirbaru village community optimizes current technology as a means of transportation, communication and marketing media, then so that the community can be independent so that the latest innovations will emerge that can improve the community's standard of living. This research uses a survey method which is still a quantitative method. This research basically involves UMKM players in telling the situation and development of their business from the past to the present, by conducting observations and interviews to collect data which will later be processed to produce results or solutions. The goal is that UMKM players can take advantage of current technology to brand their products and market their products through online media. The importance of technology to help with daily life is no surprise that most people nowadays definitely use technology, because currently technology is something that can no longer be avoided. Starting from transportation technology, communication, information and others.